2019
DOI: 10.1002/mgg3.935
|View full text |Cite
|
Sign up to set email alerts
|

TNF‐α polymorphisms affect persistence and progression of HBV infection

Abstract: BackgroundHepatitis B virus (HBV) infections are a major threat worldwide. Disease progression and outcome is diverse and depends on host genetic background. Recently, a high rate of HBV reactivation in individuals receiving tumor necrosis factor‐α (TNF‐α) antagonists showed the importance of this cytokine in HBV infection control. Here, we investigated the influence of TNF‐α promoter polymorphisms on susceptibility to chronic HBV infection (CHB), liver injury progression and outcomes.MethodsA total of 231 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…LSECs play an important role in cross presentation of Ags from virus-infected hepatocytes and promote effector CTLs to release TNF-α, which kills virus-infected hepatocytes through caspase activation [ 54 ]. A previous study also showed that TNF-α plays an important role in the inhibition of HBV reactivation [ 55 ]. The results of our present study showed that in vitro, HBc peptide could be used to restimulate hepatocytes, LSECs and KCs, and the Ag peptide was cross-presented followed by the release of notably high levels of TNF-α, IFN-γ, IL-2, IL-4 and IL-5 in supernatants.…”
Section: Discussionmentioning
confidence: 99%
“…LSECs play an important role in cross presentation of Ags from virus-infected hepatocytes and promote effector CTLs to release TNF-α, which kills virus-infected hepatocytes through caspase activation [ 54 ]. A previous study also showed that TNF-α plays an important role in the inhibition of HBV reactivation [ 55 ]. The results of our present study showed that in vitro, HBc peptide could be used to restimulate hepatocytes, LSECs and KCs, and the Ag peptide was cross-presented followed by the release of notably high levels of TNF-α, IFN-γ, IL-2, IL-4 and IL-5 in supernatants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, looking at the correlation between genetic determinants and HBeAg seroconversion will allow us to identify specific factors that may influence the worsening disease progression in HBeAg-negative patients, whose proportion has been increasing in recent years. TNF-α, as a proinflammatory cytokine, plays an important role in the clinical manifestation of various autoimmune conditions and infectious diseases [31]. Increased levels of TNF-α are observed in the plasma of CHB patients and have been associated with CHB-related liver disease progression [18,31].…”
Section: Discussionmentioning
confidence: 99%
“…TNF- α , as a proinflammatory cytokine, plays an important role in the clinical manifestation of various autoimmune conditions and infectious diseases [ 31 ]. Increased levels of TNF- α are observed in the plasma of CHB patients and have been associated with CHB-related liver disease progression [ 18 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patients undergoing ventilatory assistance are often older and are affected by other diseases, like diabetes [3], the existing comorbidities alone do not fully explain the differences in clinical severity. As demonstrated for other viral diseases, the basis of these different outcomes there are host predisposing genetic factors leading to different immunogenicity/cytokine responses as well as specific receptor permissiveness to virus and antiviral defence [4][5][6]. Similarly, during the study of host genetics in influenza disease, a pattern of genetic markers has been identified which underlies increased susceptibility to a more severe clinical outcome (as reviewed in [7]).…”
Section: Introductionmentioning
confidence: 99%